Expanded Perlite Mineral As a Natural Additive Used In Polylactide-Based Biodegradable Composites - Aksoy, Erkan; Tirkeş, Süha; Tayfun, Ümit; Tirkes, Seha; Tayfun, Ümit; Aksoy, Erkan (My University, 2024)
Polylactide (PLA) is a biodegradable polymer derived from natural resources used in various applications ranging from medical to packaging. In this study, biocomposites were developed by combining perlite mineral (PER), a natural filler material, with a biodegradable PLA matrix in incorporated contaminations of 2.5%, 5%, 10%, and 15%. The purpose of this work is to obtain composites having low production costs while retaining their main properties. Mixing force measurements, tensile, Shore hardness, impact tests, melt flow indices (MFI), and scanning electron microscopy (SEM) evaluations were carried out on composite samples to determine the processing, mechanical, melt flow, and morphological aspects of the developed composites. When the tensile test data were reviewed, minor decreases in the tensile strength and % elongation parameters were noticed with perlite loadings. The inclusion of perlite powder significantly reduced the impact strength value of PLA. Composites with high amounts of PER displayed elevated hardness values. While the MFI results were analyzed, it was deduced that the addition of PER increased the melt flow characteristics of the PLA polymer. At low PER quantities, SEM micrographs displayed that PER particles were homogeneously distributed in the PLA phase. The particle homogeneity in the composite morphology deteriorated as the PER loading ratio in the composites rose. According to the overall results, the highest performance among composites was achieved in the sample including 2.5% PER, and this sample was considered to be the most suitable option for applications regarding PLA-based biocomposite material purposes.
Keywords: Biodegradable polymer; perlite; Biocomposites; polylactide; polymeric composites